Implementasi Pendekatan Fun Learning dalam Pembelajaran Bahasa Arab melalui Program Perkampungan Bahasa Arab / Implementation of the Fun Learning Approach in Arabic Language Teaching through the Arabic Language Village Programme - Kaharuddin Kaharuddin; Hamzah Hamzah; Muh. Irwan; Ali Rahman; Ratni Bt Hj Bahri (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2026)
This study aims to analyse the implementation of the fun learning approach in Arabic language teaching through the Arabic Language Village Programme for first-year students of the Arabic Education Department at IAIN Parepare. Employing a descriptive qualitative approach, the study involved the Head of the Arabic Education Department, programme organisers, instructors, and student participants as research informants. Data were collected through observations, in-depth interviews, and documentation, and were analysed using an interactive analysis model consisting of data condensation, data display, and conclusion drawing and verification. The findings indicate that the implementation of fun learning is carried out through four interrelated stages: programme objectives, programme preparation, learning implementation, and programme evaluation. These stages form an integrated learning system that combines an Arabic language environment (bi'ah lughawiyyah) with various interactive learning activities, including language games, muḥādathah (conversation practice), Arabic songs, mufradāt (vocabulary enrichment), group discussions, and collaborative learning. This integration creates an active, communicative, participatory, and student-centred learning experience, contributing to the enhancement of students’ learning motivation, communicative competence, and self-confidence in using Arabic. This study proposes a conceptual implementation model of fun learning through the Arabic Language Village Programme as a practical and pedagogical framework that may serve as a reference for higher education institutions seeking to develop Arabic language instruction based on an immersive Arabic language environment (bi'ah lughawiyyah).Penelitian ini bertujuan untuk menganalisis implementasi pendekatan fun learning dalam pembelajaran bahasa Arab melalui Program Perkampungan Bahasa Arab bagi mahasiswa baru Program Studi Pendidikan Bahasa Arab IAIN Parepare. Penelitian menggunakan pendekatan kualitatif deskriptif dengan melibatkan Ketua Program Studi Pendidikan Bahasa Arab, panitia pelaksana, instruktur, dan mahasiswa peserta sebagai informan penelitian. Data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi, kemudian dianalisis menggunakan model analisis interaktif yang meliputi kondensasi data, penyajian data, serta penarikan dan verifikasi kesimpulan. Hasil penelitian menunjukkan bahwa implementasi fun learning dilaksanakan melalui empat tahapan yang saling terintegrasi, yaitu penetapan tujuan program, tahap persiapan, pelaksanaan pembelajaran, dan evaluasi. Keempat tahapan tersebut membentuk suatu sistem pembelajaran yang mengintegrasikan lingkungan berbahasa Arab (bi'ah lughawiyyah) dengan berbagai aktivitas pembelajaran interaktif, seperti permainan bahasa, muḥādatsah, lagu, pengayaan mufradāt, diskusi kelompok, dan pembelajaran kolaboratif. Integrasi tersebut menciptakan pengalaman belajar yang aktif, komunikatif, partisipatif, dan berpusat pada mahasiswa, sehingga berkontribusi terhadap peningkatan motivasi belajar, keterampilan berkomunikasi, serta kepercayaan diri mahasiswa dalam menggunakan bahasa Arab. Penelitian ini menawarkan model implementasi fun learning berbasis Program Perkampungan Bahasa Arab sebagai kontribusi konseptual yang dapat dijadikan acuan dalam pengembangan pembelajaran bahasa Arab berbasis lingkungan bahasa (bi'ah lughawiyyah) di perguruan tinggi.